Ultrafine-Grained Two-Phase High-Entropy Alloy Microstructures Obtained via Recrystallization: Mechanical Properties - Guillot, Ivan; Tyrman, Muriel; Perrière, Loic; Couzinié, Jean-Philippe P.; Lilensten, Lola; Prima, Frédéric; Dirras, Guy (Frontiers in Materials, 2020)
A metallurgical methodology has been set up in order to design alloys with improved mechanical properties such as strength–ductility trade-off, via improved strain hardening. To this end, a multi-concept approach including high-entropy alloys (HEAs), grain refinement, and chemical contrast and using the reversibility of the transformation-induced plasticity (TRIP) deformation mechanism has been implemented. The use of a conventional thermomechanical treatment involving cold rolling followed by an annealing stage at 650°C led to super-refined microstructures displaying an ultrafine-grained mixture (submicron size) of α (hcp) and β (bcc) phases. For Ti35Zr27.5Hf27.5Nb5Ta5 (Ti35-5-5), stress-induced martensitic transformation, and its subsequent reverse transformation during annealing at 650°C, led to a well-recrystallized state. A microstructure consisting of α and β equiaxed grains was obtained. Grain size is observed to increase within the submicron domain from about 300 to 600 nm with the holding time between 15 and 300 min. Contrariwise, for Ti35Zr26Hf26Nb6.5Ta6.5 (Ti35-6.5-6.5), which does not deform by the TRIP effect, the same thermomechanical treatment does not produce the recrystallization. Rather, precipitation of platelets in the recovered β matrix occurred. As for the mechanical properties, the yield strength of the alloys with dual-phase microstructure ranges between 950 and 1,150 MPa for Ti35-5-5 and between 850 and 950 MPa for Ti35-6.5-6.5, for annealing times ranging from 15 (higher yield strength) to 300 min (lower yield strength). This corresponds to a very large increase in the yield strength compared with that of the fully β alloys, displaying values of about 400 and 725 MPa for Ti35-5-5 and Ti35-6.5-6.5, respectively. Reasonable ductility was obtained for the alloys with optimized microstructures, which both display a tensile ductility of about 12% after annealing for 300 min at 650°C.